2019
DOI: 10.1017/wsc.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Target-site resistance to cyhalofop-butyl in bearded sprangletop (Diplachne fusca) from China

Abstract: Bearded sprangletop [Diplachne fusca (L.) P. Beauv. ex Roem. & Schult. ssp. fascicularis (Lam.) P. M. Peterson & N. Snow] is a noxious annual grass weed of paddy fields, distributed in coastal regions of the Jiangsu and Hebei provinces in China. Cyhalofop-butyl has been widely used to control grass weeds since 2006 in China. Overreliance on cyhalofop-butyl has led to the evolution of resistant weeds. In this study, the resistance level and cyhalofop-butyl resistance mechanisms were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In paddy rice systems, cyhalofop-butyl has been the predominant herbicide used to control Chinese sprangletop since 2006, which was first registered to selectively control grass weeds in China (Yuan et al, 2019). Devine (1997) reported that ACCase inhibitor resistant biotypes may evolve after 6 to 10 yr of selection pressure, especially in crop systems in which the continued use of these herbicides as the only grass weed control measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paddy rice systems, cyhalofop-butyl has been the predominant herbicide used to control Chinese sprangletop since 2006, which was first registered to selectively control grass weeds in China (Yuan et al, 2019). Devine (1997) reported that ACCase inhibitor resistant biotypes may evolve after 6 to 10 yr of selection pressure, especially in crop systems in which the continued use of these herbicides as the only grass weed control measure.…”
Section: Discussionmentioning
confidence: 99%
“…Devine (1997) reported that ACCase inhibitor resistant biotypes may evolve after 6 to 10 yr of selection pressure, especially in crop systems in which the continued use of these herbicides as the only grass weed control measure. The over-reliance application of cyhalofop-butyl in rice fields has led to resistance in some weeds, for example, Diplachne fusca (Yuan et al, 2019), Leptochloa chinensis (Peng et al, 2020) and Eleusine indica (Deng et al, 2020). Yu et al (2017) reported that repeated use of cyhalofop-butyl over the past 5 yr has led to the development of resistant Chinese sprangletop.…”
Section: Discussionmentioning
confidence: 99%
“…Cyhalofop‐butyl has been widely used to control grass weeds, including L. chinensis in rice fields for the past 20 years. Long‐term use with increasing field rates has resulted in the evolution of several resistant weed species 5–7 . In recent years, the number of cyhalofop‐butyl resistant L. chinensis has escalated in China, since the first case of resistant L. chinensis was reported in 2017 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Bearded sprangletop can become a dominant species when Echinochloa and sedges are suppressed in drill-seeded rice systems (Ceseski et al 2020). Delaying PPB application at 2.5-cm and 5.1cm depths in T3 and T4 appeared to enhance bearded sprangletop control, however; therefore, PPB treatments afforded by planting rice deeper can aid in bearded sprangletop management efforts, particularly in fields where bearded sprangletop resistance to cyhalofop may a problem (Yuan et al 2019).…”
Section: Weed Controlmentioning
confidence: 95%